2022
DOI: 10.1111/jog.15515
|View full text |Cite
|
Sign up to set email alerts
|

Third trimester re‐screening for gestational diabetes in morbidly obese women despite earlier negative test can reveal risks for obstetrical complications

Abstract: Aim We investigated associations of maternal obesity with late gestational diabetes mellitus (GDM) diagnosis (>34 weeks) in women with previous normal glucose screening, and associations of late GDM with obstetrical outcomes. Methods This retrospective cohort study assessed obstetrical and neonatal outcomes of 238 women with normal (24–28 week) glucose screening results, who underwent late repeat oral glucose tolerance tests (OGTT) (>34 weeks) due to a suspected LGA fetus (54.6%) or polyhydramnios (45.4%). A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In a Dutch cohort study, the authors reported GDM diagnoses in 23.5% of parturients who initially tested negative at 24-28 gestational weeks [3]. Similarly, other studies demonstrated around 25% late GDM 2 of 11 diagnoses in women who underwent late oGTT because of suspected large-for-gestationalage fetuses or polyhydramnios [4][5][6], with even higher rates of GDM for women with obesity [5,6].…”
Section: Introductionmentioning
confidence: 85%
“…In a Dutch cohort study, the authors reported GDM diagnoses in 23.5% of parturients who initially tested negative at 24-28 gestational weeks [3]. Similarly, other studies demonstrated around 25% late GDM 2 of 11 diagnoses in women who underwent late oGTT because of suspected large-for-gestationalage fetuses or polyhydramnios [4][5][6], with even higher rates of GDM for women with obesity [5,6].…”
Section: Introductionmentioning
confidence: 85%